Strategi Kreatif Guru Seni Budaya Di Tengah Pandemi Covid-19 - Adhetya Cahyani; Erni Munastiwi; Nur Imam Mahdi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
At this time the teaching and learning activities also experience changes that is done remotely and using an online or online system. This study aims to find out how creative strategies are carried out by art and culture teachers in one of the high schools in the middle of the Covid-19 pandemic situation. This study uses qualitative research methods, a type of case study. The results showed that the strategy carried out by the subject was in accordance with the theory of the characteristics of the creative teacher consisting of 4 points namely fluency, flexibility, originality and elaboration. Fluency, the subject is able to produce ideas that are in accordance with the problem that is compiling assignments such as making clippings, summarizing, practicing dancing with family and making covid-themed dialogues. Flexibility, the subject is able to open his mind by seeing the current situation, such as bringing up creative ideas, innovative and freeing students to use all available sources. Originality, the subject created new ideas such as the task of practicing dancing with family members then made a dialogue with regional languages about covid-19. Elaboration, subjects are able to see a problem in detail by adjusting government recommendations.